Incorporation of pollen flour in baking’s - Lazcano-Hernandez, Martin Alvaro; Navarro-Cruz, Addi Rhode; Sanches, Raul Ávila-Sosa; Hernandez-Abundez, José Alejandro; Zeron-Alvarado, Cintia Abigail; Pereira, Daniel Santiago (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2019)
Every day invariably a popular consumption food in the weekly table and at any time of the day is bread, currently for sectors of the population the change in flavors, textures and composition have boom in the trade. The substitution of wheat flour with different cereals, legumes or functional ingredients encompasses space in traditional bakeries as well as bakeries in the commercial center. Bee pollen is a healthy food because it has 30-35% protein, is found in the form of essential amino acids above the standard. Its layers of ectin and exine allow the pollen not to be so digestible to the human being, so a baked product would favor its use. This research will establish the appropriate formulation to integrate the flour of pollen to a bread dough until where sensorially the addition is not detected, as well as to standardize the methodology of bakery. Taking into account parameters such as: quantity of flour wheat-pollen and sugar y/o honey, fermentation time, baking time and baking temperature. The product obtained is sensorially valued to determine the concentration of flour and which is the percentage of addition best evaluated sensory, the accepted range of addition is 5 to 10% substitution of wheat flour. Sensorially there is no difference in attributes such as color, odor, flavor, consistency and texture in this range, being slightly better the flavor of 10% of pollen flour. However the white bread obtained can be marketed up to 10% of addition, being alternative of the beekeepers to obtain extra profits not only from the sale of honey.